KALMUL Software Assited by GeoGebra (A New Media for Learning Multivariable Calculus) - Utami Zuliana, Sri; Arfinanti, Nurul; Damar Jati, Wahyu; Ramadhan, Fadlilah Aziz (Quadratic: Journal of Innovation and Technology in Mathematics and Mathematics Education, 2023)
Multivariable calculus is one of the compulsory subjects for study programmes in the fields of science and technology. The graphical approach to of two variable calculus written in a book or board usually makes it difficult for students to understand. This research aims to build a tool for learning multivariable calculus using GeoGebra. GeoGebra provides three-dimensional visualization facilities through the GeoGebra 3D Graphing Calculator software. This software has an android application so that it can be accessed via a smart phone. This research developed learning media for multivariable calculus using GeoGebra software in the form of an android application. The lecture material is limited to multivariable derivative. The research method used in this study is research and development (R & D) with development of 4-D models (Four D) for research design. The design of this study includes four main stages, namely the definition phase, the design stage, the development stage, and the dissemination stage. The results of validating media products are in good criteria and the results of small and large scale tests are very good criteria.